2018
DOI: 10.1186/s12978-018-0607-3
|View full text |Cite
|
Sign up to set email alerts
|

Condom use at last sex by young men in Ethiopia: the effect of descriptive and injunctive norms

Abstract: BackgroundCondoms are an important prevention method in the transmission of HIV and sexually transmitted infections as well as unintended pregnancy. Individual-level factors associated with condom use include family support and connection, strong relationships with teachers and other students, discussions about sexuality with friends and peers, higher perceived economic status, and higher levels of education. Little, however, is known about the influence of social norms on condom use among young men in Ethiopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Previous studies have showed that education play a big role in curbing HIV/AIDS and this is consistent with this study as we found education statistically associated with HIV knowledge [14,34].Many studies showed that Early Antiretroviral Therapy (ART) and condom use can prevent transmission of HIV/ AIDS and this can lower the incidence of the infection hence controlling the spread of the disease [2][3][4][5]. Previous studies revealed that testing and counselling have shown a successful story since this helps in early case detection and early treatment which has played a major role in preventing mother to child transmission (MTCT) therefore this should continue to be scaled up as a public health strategy to prevent transmission of HIV/AIDS [10], [11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have showed that education play a big role in curbing HIV/AIDS and this is consistent with this study as we found education statistically associated with HIV knowledge [14,34].Many studies showed that Early Antiretroviral Therapy (ART) and condom use can prevent transmission of HIV/ AIDS and this can lower the incidence of the infection hence controlling the spread of the disease [2][3][4][5]. Previous studies revealed that testing and counselling have shown a successful story since this helps in early case detection and early treatment which has played a major role in preventing mother to child transmission (MTCT) therefore this should continue to be scaled up as a public health strategy to prevent transmission of HIV/AIDS [10], [11].…”
Section: Discussionsupporting
confidence: 90%
“…Prevention of HIV-1 infection with Early Antiretroviral Therapy (ART), HIV pre and post exposure prophylaxis (PrEP) (PEP), condom use has been a successful story in sub-saharan Africa and throughout the continent. Antiretroviral therapy that reduces viral replication could limit the transmission of human immunodeficiency virus type 1 (HIV-1) in serodiscordant couples [2][3][4][5][6][7]. Many studies has shown that sexuality education is key in prevention of HIV and related sexually transmitted diseases especially if given to adolescents, schools and many people those that receive sex education are likely not to indulge in risky sexual behaviours [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the Nepal government’s effort to make the condoms easily available and accessible, their use is low among male college youth. In countries such as Southern Brazil, China, Canada, United States, Ethiopia the prevalence of condom use in the last sexual intercourse among university students was 61.4%, 44.2%, 47.2%, 63.8%, and 55.8% respectively [ 24 28 ]. This difference might be due to the knowledge level about the condoms and youth’s attitude to use them within and outside the country.…”
Section: Discussionmentioning
confidence: 99%
“…The conceptual definition of the key study constructs and the measures, including social norms, norm violations, individualism-collectivism, and tightness-looseness, were adapted from existing literature developed in the U.S and translated into each country's official language following the procedures outlined by Brislin (1986); validity and reliability evidence was provided. Likewise, Jain et al (2018) investigated the effect of descriptive and injunctive norms on condom use among young men in Ethiopia using norms measures from the TNSB (Rimal and Real, 2005) translated into Amharic, Afan Oromo, and Tigrigna. Adaptations were made in the norm measures to account for cultural context, but measurement validity and reliability evidence was not presented.…”
Section: Universalismmentioning
confidence: 99%